2017
DOI: 10.1103/physrevd.95.084037
|View full text |Cite
|
Sign up to set email alerts
|

Generic rotating regular black holes in general relativity coupled to nonlinear electrodynamics

Abstract: We construct regular rotating black hole and no-horizon spacetimes based on the recently introduced spherically symmetric generic regular black hole spacetimes related to electric or magnetic charge under nonlinear electrodynamics coupled to general relativity that for special values of the spacetime parameters reduce to the Bardeen and Hayward spacetimes. We show that the weak and strong energy conditions are violated inside the Cauchy horizons of these generic rotating black holes. We give the boundary betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 99 publications
(179 reference statements)
0
93
2
Order By: Relevance
“…Recently, one of us has proposed a new procedure [77,78], in which one simply drops the complexification step of the Newman-Janis algorithm. The procedure has been applied to various cases [27,40,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. One of the main purposes of this paper is to construct the rotating LQBH solution by using this new procedure, and then to investigate its main geometric properties and the effects of LQG on the shadow of the rotating LQBH solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one of us has proposed a new procedure [77,78], in which one simply drops the complexification step of the Newman-Janis algorithm. The procedure has been applied to various cases [27,40,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. One of the main purposes of this paper is to construct the rotating LQBH solution by using this new procedure, and then to investigate its main geometric properties and the effects of LQG on the shadow of the rotating LQBH solution.…”
Section: Introductionmentioning
confidence: 99%
“…In this frame the stress-energy tensor is naturally diagonal (ρ, P 1 , P 2 , P 3 ), whose components [45,50]. In particular, at the equatorial plane (θ = π/2) they have the following form:…”
Section: Horizon Properties and Weak Energy Conditionmentioning
confidence: 99%
“…The metric (1) with mass function (2) is used throughout this paper. The magnetic charge can be expressed as [13][14][15]…”
Section: A Generic Black Hole Spacetimementioning
confidence: 99%
“…[14] authors suggested the regular black hole models as the gravitational field of a non-linear electric or * jaroslav.vrba@fpf.slu.cz † ahmadjon@astrin.uz ‡ arman.tursunov@fpf.slu.cz § ahmedov@astrin.uz ¶ zdenek.stuchlik@fpf.slu.cz magnetic monopole. The properties of the rotating analogue of this type black hole have been considered in [15].…”
Section: Introductionmentioning
confidence: 99%